Pengaruh Brand Authenticity dan Brand Awareness Terhadap Purchase Intention dengan Brand Engagement sebagai Moderasi pada Industri Kecantikan - Khoirunisa, Dhea Amanda; Indriasari, Dewi Pratiwi (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of Brand Authenticity and Brand Awareness on Purchase Intention with Brand Engagement as a moderating variable in the beauty industry in the Tangerang region. This study emphasizes the importance of companies in highlighting the value of Brand Authenticity, increasing Brand Awareness, and strengthening consumer emotional involvement through Brand Engagement to create a more authentic and relevant brand experience. The research method used is quantitative with a purposive sampling technique on 120 respondents. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results show that Brand Authenticity and Brand Awareness have a positive effect on Purchase Intention, which means that the higher the consumer's perception of brand authenticity and the level of brand awareness, the higher the consumer's tendency to make a purchase. In addition, Brand Engagement is proven to be able to moderate and strengthen the relationship between Brand Authenticity and Purchase Intention as well as between Brand Awareness and Purchase Intention. These findings indicate that consumer engagement with a brand can increase the effectiveness of both variables in driving consumer purchase intention and strengthening the brand's position in the Indonesian beauty market.